PENGARUH PENERAPAN ICT (INFORMATION, COMMUNICATION, TECHNOLOGY) TERHADAP SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN KINERJA ORGANISASI DENGAN BUDAYA SEBAGAI VARIABEL MODERASI - Sembiring, Evi Dora; Bastian, Elvin; Ramdhani, Dadan (Bussman Journal : Indonesian Journal of Business and Management, 2021)
This study aims to find empirical evidence about the influence of Influence Application of ICT (Information, Communication, Technology) against the accounting information systems in improving organizational performance with culture as a moderating variable (Empirical Study on manufacturing companies in Cilegon). The sampling method used in this research is purposive sampling method and obtained samples are 75 employees at the company's existing manufacturing city of Cilegon. Data were analyzed using the software Partial Least Square (PLS). Research shows that a variable scheme of ICT (Information, Communication, Technology) positive effect significantly to the accounting information system, a variable scheme of ICT have a positive influence significant in improving the performance of the organization with a culture as a moderating variable and accounting information systems have a positive influence significantly on the performance of the organization (Empirical Study on manufacturing companies in Cilegon).